Clients' Perspectives of the Effectiveness of Home Modification Recommendations by Occupational Therapists. Issue 3 (3rd July 2018) - Lau, Guby Wai Chu; Yu, Mong-Lin; Brown, Ted; Locke, Cassandra
Abstract: This study investigates the effectiveness of home modifications from clients' perspectives. Ten participants who received home assessments and modification recommendations were recruited from a rehabilitation agency. The dimension of home measure and qualitative interviews was conducted. The interviewers were transcribed verbatim and analyzed thematically. Participants found home modifications improved their safety, accessibility, privacy, and occupational performance, especially in performing self-care activities. Occupational therapists provided sufficient information and actively involved clients/carers in the decision-making process, which contributed to clients' perspectives of satisfaction and effectiveness with completed modifications.